Rubidium Multication Perovskite with Optimized Bandgap for Perovskite‐Silicon Tandem with over 26% Efficiency. Issue 14 (4th April 2017) - Duong, The; Wu, YiLiang; Shen, Heping; Peng, Jun; Fu, Xiao; Jacobs, Daniel; Wang, Er‐Chien; Kho, Teng Choon; Fong, Kean Chern; Stocks, Matthew; Franklin, Evan; Blakers, Andrew; et al.
Abstract : Rubidium (Rb) is explored as an alternative cation to use in a novel multication method with the formamidinium/methylammonium/cesium (Cs) system to obtain 1.73 eV bangap perovskite cells with negligible hysteresis and steady state efficiency as high as 17.4%. The study shows the beneficial effect of Rb in improving the crystallinity and suppressing defect migration in the perovskite material. The light stability of the cells examined under continuous illumination of 12 h is improved upon the addition of Cs and Rb. After several cycles of 12 h light–dark, the cell retains 90% of its initial efficiency. In parallel, sputtered transparent conducting oxide thin films are developed to be used as both rear and front transparent contacts on quartz substrate with less than 5% parasitic absorption of near infrared wavelengths. Using these developments, semi‐transparent perovskite cells are fabricated with steady state efficiency of up to 16.0% and excellent average transparency of ≈84% between 720 and 1100 nm. In a tandem configuration using a 23.9% silicon cell, 26.4% efficiency (10.4% from the silicon cell) in a mechanically stacked tandem configuration is demonstrated which is very close to the current record for a single junction silicon cell of 26.6%. Abstract : Rubidium doping improves the crystallinity and suppresses the defect migration in the 1.73 eV bandgap perovskite, which lead to improvement in cell performance and light stability. Semi‐transparent perovskite cell with efficiency of 16% and average transparency of 84% between 720 and 1100 nm is fabricated. By combining with 23.9% silicon cell, efficiency of 26.4% for four terminal tandem is obtained.